Twenty Years of SpayVac® Research: Potential Implications for Regulating Feral Horse and Burro Populations in the United States - Ursula S. Bechert (Human-Wildlife Interactions, 2018)
There are currently >75,000 feral horses (Equus ferus caballus) and burros (E. asinus ) on U.S. public lands, yet the Appropriate Management Level (AML) is set at just under 27,000. Wildlife managers, conservation biologists, and livestock ranchers are concerned about the impacts that these free-ranging horses have on shared rangelands. Immunocontraceptive vaccines may have the greatest potential to regulate horse population numbers once AML is reached; however, the vaccine must have multi-year efficacy to be both technically feasible and cost-effective. Immunocontraception based on porcine zona pellucida (PZP)-specific antigens is highly tissue-specific, targeting the ova, and blocking sperm binding through antibody occupation of ZP receptors on the ova. ZonaStat-H and PZP-22 are PZP-based vaccines; however, their contraceptive efficacy does not last long enough to meet management needs. SpayVac® achieves multi-year efficacy with a single dose, without boosters, because the PZP antigens are encapsulated within liposomes (multi-layered, submicroscopic vesicles), which gradually release PZP glycoproteins to antigen-presenting cells over an extended period of time. We review results from SpayVac trials in horses and other species to deepen our understanding of how the vaccine works and how it may best be applied to regulate free-ranging horse populations at AML. We examine 3 studies in horses, which used different SpayVac formulations and delivery methods, to learn more about the relationship between antibody titers and contraceptive efficacy, as well as potential mechanisms of action (e.g., preferential stimulation of IgG4/7 antibody isotypes). Additional research to explore possible effects of injection site location, antigen purity, role of PZP antibodies, and different formulations (e.g., dose, adjuvant) is needed for efficacious application to free-ranging herds.